Upper Gastrointestinal Bleeding Due to Idiopathic Oesophageal Ulceration in the Era of HAART: A Vanishing yet Pernicious Aetiology - Sofia Nigar; Tagore Sunkara; Mel A Ona; Vinaya Gaduputi; Madhavi Reddy (Journal of Clinical and Diagnostic Research, 2017)
Oesophageal ulcers are a rare cause of upper Gastrointestinal Bleeding (GIB). In patients with Acquired Immune Deficiency Syndrome (AIDS), oesophageal diseases including oesophageal ulcers are very common. Idiopathic Oesophageal Ulcers (IOU) comprises a subgroup of oesophageal ulcers with no identifiable cause. IOU mainly present as odynophagia, retrosternal chest pain, decreased oral intake, and weight loss. Upper GIB is a rare presentation. In the era of Highly Active Anti Retroviral Therapy (HAART), with improvement in CD4 count, this entity is almost forgotten.